Characteristics Of Vegetation In Various Agroforestry Land Covers And Physical Properties Of Soil In Mandiangin Forest, South Kalimantan - Alfiyah, Faiqotul; Wijayanto, Nurheni; Hartoyo, Adisti Permatasari Putri (Journal of Tropical Silviculture, 2024)
Land use changes in forest areas for specific purposes (KHDTK)in Mandiangin, South Kalimantan affect the vegetation diversity loss and physical soil properties changes. This study aimed to analyze vegetation characteristics and soil physical properties across different land cover types (rubber/RB, bare land/BL, simple agroforestry/SA, complex agroforestry/CA, and natural forest/NF) on various slope positions (above, middle, and bottom). The method used was purposive sampling for vegetation analysis in 5 land cover types and 3 slope positions with three replications (45 plots). Parameters observed for soil physical properties were Bulk Density (BD), Particle Density (PD) and Porosity The total number of individuals in NF, SA, CA, RB, and BL in order is (1,713,333, 1,035,000, 768,333, 444,167, 375,000 individuals/ha individuals). The dominant species in natural forests are alaban and bangkal gunung, complex agroforestry namely rambutan, durian, nangka, avocado, matoa and mahoni, simple agroforestry namely jengkol, kemiri and mahoni, rubber plantations namely karet, bare land namely karamunting. The highest bulk density was found in natural forest and rubber (1.21 g/cm³). The highest porosity was found in bare land (53.34%) and the lowest in rubber (44.57%). These findings indicate that variations in land cover and slope significantly affect soil physical properties, which is important for sustainable land management. Keywords: Agroforestry, land use covers, soil physical properties